Stimulation of Apoptosis in Michigan Cancer Foundation-7 Human Breast Cancer Cell Line by Whole Plant Ethanolic Extract of Enicostemma axillare through Extrinsic and Intrinsic Pathway - Gunasekaran, Krishnamoorthy (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: With the increasing level of resistance to chemotherapy and radiotherapy and the associated toxicity of these therapies, the uses of plant-based compounds are gaining importance. This study was done to prove the apoptotic potential of Enicostemma axillare in breast cancer cells. Materials and Methods: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay was performed involving the treatment of Michigan Cancer Foundation-7 cells for 24 h with ethanolic extract of E. axillare (EEEA) and doxorubicin to assess the cell viability, lactate dehydrogenase (LDH) was done to assess cytotoxicity, ethidium bromide (EtBr) and acridine orange (AO) assay was done to assess nuclear morphology of apoptotic cells and the expression of proteins associated with apoptosis â€“ Bad, Bcl2, Bax, CytoC, Caspase 3, 8, and 9 were analyzed by western blotting. The data are expressed as meanÂ±SEM. Results and Discussion: IC50 value for EEEA is 12.5 Î¼g/ml, whereas for doxorubicin is 1 Î¼g/ml. A significant increased level of LDH release is seen in treated groups. EEEA and doxorubicin decrease cell viability. In AO/EtBr staining, the live cells of the EEEA treatment were similar to that of the doxorubicin. Cells stained green represent viable cells, whereas bright red staining represents late apoptotic cells. EEEA down-regulated the expression of Bcl2 (antiapoptotic protein) and up-regulated the expression of Bad and Bax (proapoptotic proteins) in MCF-7 cell line compared to control cells. In this study, EEEA treatment significantly increased the protein expression of caspase-3, 8, and 9 compared to control. Conclusions: Our finding showed that EEEA induces extrinsic and intrinsic pathway mediated apoptosis. Thus, E. axillare raises new hope for its use in breast cancer therapy.